Tracheostomy in COVID-19 patients and its effect on laboratory parameters: a retrospective case series - Amel Krkalić (Medicinski glasnik, 2023)
Aim: To evaluate characteristics of COVID-19 tracheostomy and its effect on laboratory parameters. Methods: Demographic parameters, duration indicators, and laboratory parameters before and after tracheostomy were analysed in a series of 17 patients with COVID-19 patients. Results: Of the 17 patients, four were males and 13 females with a mean age of 59 years. The average length of total hospitalization was 12 days, the length of stay in intensive care was 10 days, the length of endotracheal intubation was 9 days; tracheostomy was mostly performed on the seventh day. There was a significant correlation between comorbidities and outcomes; however, laboratory parameters did not show statistical significance. Conclusion: Open surgical tracheostomy is recommended in all COVID-19 critically ill patients within 1 or 2 weeks after endotracheal intubation; it can be performed in terms of renal laboratory parameters, lactate and D-dimer. These patients had a lower possibility of weaning from mechanical ventilation.
Keywords: D-dimer; demographic; endotracheal intubation; lactate; weaning